2018
DOI: 10.29088/sami/ajca.2018.3.1231
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of two-dimensional gas chromatography time-of-flight mass spectrometry retention times of 160 pesticides and 25 environmental organic pollutants in grape by multivariate chemometrics methods

Abstract: A B S T R A C TA quantitative structure-retention relation (QSRR) study was conducted on the retention times of 160 pesticides and 25 environmental organic pollutants in wine and grape. The genetic algorithm was used as descriptor selection and model development method. Modeling of the relationship between the selected molecular descriptors and retention time was achieved by linear (partial least square; PLS) and nonlinear (kernel PLS: KPLS and Levenberg-Marquardt artificial neural network; L-M ANN) methods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The application of this model for two NIR datasets showed that the technique provides good prediction performance, and it outperformed the classical models. Amini et al [16] reported that QSRR was used to determine and predict the retention factor of 160 different pesticides and 25 environmental organic pollutants in grape and wine. Modeling of the relationship between the selected molecular descriptors and retention time was achieved by linear [partial least square(PLS)] and nonlinear [kernel PLS(KPLS) and Levenberg-Marquardt ANN(L-M ANN)] methods.…”
Section: Introductionmentioning
confidence: 99%
“…The application of this model for two NIR datasets showed that the technique provides good prediction performance, and it outperformed the classical models. Amini et al [16] reported that QSRR was used to determine and predict the retention factor of 160 different pesticides and 25 environmental organic pollutants in grape and wine. Modeling of the relationship between the selected molecular descriptors and retention time was achieved by linear [partial least square(PLS)] and nonlinear [kernel PLS(KPLS) and Levenberg-Marquardt ANN(L-M ANN)] methods.…”
Section: Introductionmentioning
confidence: 99%